An Empirical Study On Users Perception Towards Mobile Commerce In Malaysia - Jayamani, Jegan Mogan (2003)
This study aims to investigate the ever-increasing information technology from the angle of Mobile Commerce. The study proved that Mobile Commerce is the new way of doing business.